The Strategy of “Sekolah Sak Ngajine” in Developing Students’ Religious Values - Rina Annisa (Institut Studi Islam Muhammadiyah Pacitan, 2025)
The `Sekolah Sak Ngajine` program is an enrichment initiation program to improve student competence in mastering material and student skills in implementing religious teaching practices through the learning process and habituation in daily life at school. In this modern era, the program is very important in improving Islamic character and fostering students’ religious values. This research method is qualitative with and type of case study research. Data collection techniques are in-depth interviews, participatory observation, and documentation. Data analysis techniques in the study are Individual Case Analysis through data condensation, data presentation (data displays), c) drawing conclusions or verification (verification). Cross-case analysis by formulating propositions based on the findings of the first case then continued with the second case, comparing and integrating theoretical findings from both research cases, and formulating conclusions. The results of this study are 1) The PAI teacher’s delivery strategy is a method in delivering drills and habits, teacher techniques as an effort to foster religious values in students are advice, examples, and practices. 3) The PAI teacher’s management strategy is management with daily and weekly schedules, written/oral tests during semester exams, controlling/controlling religious values with guidance and supervision, and the form of religious values that emerge is being accustomed to reading the Qur’an, praying dhuha and dhuhur in congregation, yasin tahli istigotsah, not saying dirty words, maintaining behavior inside and outside the classroom, and bowing in front of the teacher, and covering the genitals.